2022
DOI: 10.35378/gujs.885345
|View full text |Cite
|
Sign up to set email alerts
|

The Current-Voltage Characteristics for Electrode Geometry Model of Positive DC Corona Discharge in Air

Abstract: Highlights• This paper focuses on the (I-V) characteristics calculations of the corona discharge.• The numerical calculation approach uses the concept of the electrode geometry model. • There is an accuracy high degree between the numerical calculations and the research data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…This study will use the Eq. ( 2) model as a reference in the calculation of the (I-V) characteristic model, with constant C being a geometric function of the capacitance as proposed by [14,15]. The capacitance function in the corona discharge is different from the capacitance function in the case of ordinary electricity [23,24].…”
Section: Mathematical Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…This study will use the Eq. ( 2) model as a reference in the calculation of the (I-V) characteristic model, with constant C being a geometric function of the capacitance as proposed by [14,15]. The capacitance function in the corona discharge is different from the capacitance function in the case of ordinary electricity [23,24].…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…The pointed angle at the tip of the active electrode is =2. This study uses variations in the angle  not found [14,15] and variations in the distance between the two electrodes. This study is significant.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations